2022
DOI: 10.3389/fphar.2022.896601
|View full text |Cite
|
Sign up to set email alerts
|

Nonerythropoietic Erythropoietin Mimetic Peptide ARA290 Ameliorates Chronic Stress-Induced Depression-Like Behavior and Inflammation in Mice

Abstract: Major depressive disorder (MDD) is a highly prevalent psychiatric disorder. But the treatment of depression remains challenging. Anti-inflammatory treatments frequently produce antidepressant effects. EPO-derived helix-B peptide ARA290 has been reported to retain the anti-inflammatory and tissue-protective functions of EPO without erythropoiesis-stimulating effects. The effects of ARA290 on MDD remain elusive. This study established chronic unpredictable mild stress and chronic social defeat stress mouse model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 55 publications
1
2
0
Order By: Relevance
“…21 As anticipated, this study revealed no significant changes in peripheral blood erythropoietic parameters, serum AST, ALT, LDH, and spleen weight and length after ARA290 treatment. As mentioned earlier, the anti-apoptotic and anti-inflammatory activities of ARA290 have been confirmed by previous studies in various models, 22,23 and our results further demonstrated that these ARA290 effects extend to cerebral ischemic models. Untargeted LC-MS/MS analyses revealed that the primary differential metabolites affected by ARA290 were associated with the pathophysiology of the vascular endothelium, which may be related to its anti-apoptotic and anti-inflammatory properties.…”
Section: Temporal Changes In β Cr Protein Levels Are Related To Degre...supporting
confidence: 91%
“…21 As anticipated, this study revealed no significant changes in peripheral blood erythropoietic parameters, serum AST, ALT, LDH, and spleen weight and length after ARA290 treatment. As mentioned earlier, the anti-apoptotic and anti-inflammatory activities of ARA290 have been confirmed by previous studies in various models, 22,23 and our results further demonstrated that these ARA290 effects extend to cerebral ischemic models. Untargeted LC-MS/MS analyses revealed that the primary differential metabolites affected by ARA290 were associated with the pathophysiology of the vascular endothelium, which may be related to its anti-apoptotic and anti-inflammatory properties.…”
Section: Temporal Changes In β Cr Protein Levels Are Related To Degre...supporting
confidence: 91%
“…Moreover, a study conducted by Xu et al further validated the anti-inflammatory effect of ARA290. Daily administration of ARA290 could ameliorate depression-like behavior during chronic stress induction in mouse models via reducing neutrophils in the bone marrow and meninges [25]. Here, we tested the efferocytosis ability of Pg.…”
Section: Discussionmentioning
confidence: 99%
“…EPO and non-erythropoietic derivatives have also shown potential pro-cognitive effects in psychiatric disorders [ 60 ]. The non-erythropoietic derivative ARA290 can reduce inflammation and depression, which prolongs stress in rodents [ 61 ]. Studies have found that MDD may be related to neuronal plasticity damage8.…”
Section: Discussionmentioning
confidence: 99%